Impact of rituximab therapy on endothelial function and other markers of atherosclerosisin patients with active rheumatoid arthritis - Aleksandr Vital'evich Volkov; O G Lineva; K Kh Kuzikyants; G V Lukina; E L Nasonov; Aleksandr Vitalyevich Volkov; O G Lineva; K Kh Kuzikyants; G V Lukina; E L Nasonov (Научно-практическая ревматология)
Endothelial dysfunction plays a key role in the pathogenesis of atherosclerosis. An increased cardiovascular risk in patients with rheumatoid arthritis (RA) suggests that inflammation is of importance for the occurrence and progression of atherosclerosis. Rituximab (RTM, monoclonal antibodies to CD20-positive B lymphocytes) is used to treat patients with active RA. Objective. To evaluate the effect of RTM on endothelial function in patients with active RA. Subjects and methods. The study enrolled 20patients with active RA (DAS 28 >5.0); their mean age was 50 (range 41.5 to 63) years; mean disease duration was 95.7 (range 24 to 144) months. Intravenous RTM was used (as a course of 2 infusions in a dose of 1000 mg at a 2-week interval) in all the patients. Brachial artery flow-dependent vasodilation (FDVD) that was carried out in all the patients at screening (before the first infusion) and also at 2, 8, 16, and 24 weeks after the second infusion was employed to evaluate endothelial function. Results. Before RTM therapy, the study group of patients showed no statistically significant deviations of FDVD values from those in the gender- and age-matched control group. FDVD correlated with age (r=-0.44; p=0.049), disease duration (r = 0.6; p=0.017), cholesterol level (r=0.48; p=0.045), common carotid artery intima-media thickness (r=0.52; p=0.023), and cardiovascular risk factors (r=0.51; p=0.027). No statistically significant differences were found in the baseline value of FDVD and those observed after a course of RTM therapy and at weeks 8, 16, 24 (12.8±5.7, 11.3±5.2, 14.3±7.1, and 12.5±5.2%, respectively). All the patients were divided into 2 groups according to their response (an increase or a reduction in FDVD over time). Group 1 patients (n=10) demonstrated a significant increase in this index from 10.74±5.75 (at screening) to 14.17±5.13% (at week 24) (p